Caracterização sedimentológica e geoquímica de rochas microclásticas da Formação Ponta Grossa (Bacia do Paraná) em um arcabouço estratigráfico sequencial - Rodrigues, Maria Clara dos Reis (2024)
A significant portion of the sedimentary geological record comprises microclastic rocks, which are predominantly formed by particles smaller than 0.062 mm. In Brazil, these rocks are extensively studied from a geochemical and paleontological perspective, but still lack detailed descriptions and classifications primarily due to the difficulty in observing their minute particles and structures. This necessitates meticulous study, often requiring sophisticated equipment, resulting in few works that integrate different analytical techniques and scales of observation. Based on this, the present study aims to: (i) characterize the textural and compositional (through facies and microfacies) and geochemical (TOC and Rock-Eval pyrolysis) aspects of microclastic rocks from the Ponta Grossa Formation (Devonian of the Paraná Basin), which constitute two third-order transgressive-regressive (T-R) sequences; and, using the sequential stratigraphic framework previously established by Plantz (2021), (ii) conduct a comparative analysis of the textural, compositional, and geochemical data obtained for each analyzed sequence. The selected intervals are: D200, corresponding to the Jaguariaíva Member, and D500, representing the initial deposits of the São Domingos Member of the Ponta Grossa Formation (Devonian of Paraná Basin). The sequences are located between 345.3 – 290.6 m and 211.6 – 168.0 m depth from the core of well 2-TB-1-PR, sampled continuously up to 451.6 m, on the eastern edge of the Paraná Basin. As results, seven sedimentary facies were identified: M1 and M2 encompass finely laminated shales and siltstones with streaked bedding; M3 and M4 siltstones with varying intensities of bioturbation and clay content; H1 and H2 rocks with lenticular heterolithic bedding, and H3 rocks with flaser heterolithic bedding. The microfacies (M1a, M2a, M2b, M3a, M3b, M4a, M4b, H1a, and H3a), defined from petrographic thin section descriptions, provide even greater detail to the facies. Facies and microfacies indicate deposition in a shallow marine, platformal environment, between the shoreface (middle to lower) and offshore (upper to lower), subject to the constant action of storm waves. Besides the constant influx of silt from the remobilization of sediments from the inner to the outer platform during high-energy events, there is input of continental sediments, as indicated by the recurrence of type III organic matter associated with type II, suggesting that hyperpycnal flows should also be considered as agents for the remobilization of sediments to the offshore. From an exploratory standpoint, the values of TOC, S2, and S1+S2 reach a maximum of 2.41%, 9.47 mg HC/g rock, and 10.99 mg HC/g rock, respectively. When combined with the predominant mixture of type II and III organic matter, this allows the conclusion that, in general, the rocks of the analyzed T-R sequences do not exhibit good generation potential. Besides the quantification of organic matter and characterization of its origin, thermal evolution is essential for characterizing the generation potential of the rocks. For this purpose, in addition to Tmáx and PI, diagenetic minerals (geothermometers) were used, indicating that the rocks reached mesodiagenesis, with temperatures up to 130 °C, approximately corresponding to the transition between the immature and mature zones (Tmáx close to 440 °C). Similar information was obtained through geochemical assays. Despite all this, some samples, mainly from facies M1 and M2 present in the TST's of the analyzed T-R sequences, exhibit good generation potential and are in the mature zone.